(untitled) (Revista Electrónica REDINE, 2018)
Then an essay calling on management thinking from the teacher innovation and heuristics is presented. Teachers in addition to their cognitive skills, must innovate and promote improvements to strengthen the process of andragogical learning. This new educational management as Hargreaves (2005), "involves social and cultural components as well as technical and intellectual, to establish emotional bonds with and among students, and thus lay the foundation construction of empathy, tolerance and commitment society "(p. 59). This context leads to new challenges for teachers in universities, in addition to encouraging the growth of the human being, allows the coexistence and the common good.